Proyecto de factibilidad para la creación de una empresa productora y comercializadora de balanceado para aves en el Cantón Paltas Provincia de Loja - Campoverde García, José Julio (2016)
To start with the study of this project, it has set an overall target called "FEASIBILITY STUDY FOR THE IMPLEMENTATION OF A COMPANY PRODUCER AND DISTRIBUTOR OF BALANCED FOR BIRDS IN Paltas Canton Loja province" as an alternative to poultry producers of the town have a quality product at a low price, specific objectives that served as a guide for the study were raised. In the market study proceeded to the collection of information by applying a survey of 375 families in the canton Paltas, then be tabulated, processed and interpreted so as to present the results and thus determine the unmet demand for 20,800 quintals balanced at the start of the year of study and marketing strategies for the product. The Technical Study is based on an analysis of all requirements for the location of the Company, a technical drawing of the adjustments was made considering the specifications of the local capacity was determined to install that will be 87,360 quintals a year and the percentage will be used to produce, that will leave 24% of capacity. Also noted is the process description, flow diagrams for the preparation and service delivery. Organizational Study of the company is based on the different rules and regulations in order to facilitate a smooth operation, describes the elements necessary for the administration and the business structure, hierarchical levels, minuta, flowcharts and manual functions. In the Financial Study was based Market Research and Technical allowing identify needs, using tools such as budget to quantify the amount required for investment and thereby determine the sources of raising capital. Within the Financial Evaluation it is based on key economic indicators such as: Net Present Value, Internal Rate of Return, Benefit-Cost Ratio and Sensitivity Analysis through which the profitability of the project was determined. After establishing the project we conclude that: the market study in the Paltas Canton, helped determine that the project can be executed by the results obtained in the analysis of demand, supply and marketing levels . The company benefit jobs. For the implementation of this project a capital of $ 76.338,07 the same to be financed from internal sources the 47.60% and 52.40% the external source is required, the loan it held at the Ban Ecuador BP, with 11.83% interest. The cost is $ 24.32 quintal dollar profit 24% being its retail price of $ 30, and this competitive market price. When performing the financial analysis is the net present value of 206,332.53 the Capital recovery period is 1 years 6 months and 14 days; the cost benefit ratio is 1.24; the internal rate of return is 93.25%; when making an increase in costs of up to 15.58% the project is not sensitive; and, when performing a decrease in revenues of up to 12.60% the project is not sensitive; allowing to observe the project if feasible, for implementation